ANALYSIS OF THE USE OF CODE MIXING IN INSTAGRAM POSTS AS A BRAND IMAGE STRATEGY FOR LOCAL BRANDS - Lira Mey Nisa; Octavia Amelia, Nijmal Adawiyah, Yolanda Marchella (Adisam Publisher, 2024)
Through Critical Discourse analysis, the research aims to analyze the use of code- mixing in Instagram posts by Indonesian local brands and its impact on brand image. The use of code-mixing in a local brand's Instagram post is the main concern of the researcher. Using Fairclough's Critical Discourse Analysis theory, which consists of text dimensions, discourse practices, and social practices, data in the form of captions of local brands' Instagram posts from the @erigostore Instagram account were analyzed to identify patterns of code-mix use and evaluate its impact on brand image. The total data analyzed was 10 Instagram posts through Erigo's official account. The results show that code-mixing enhances Erigo's sense of modernity and practicality, proximity to Audience, professionalism, and reflects openness to global influences. This strategy reinforces Erigo's image as a brand that follows trends, is familiar with its bilingual audience, and is competitive in the international market. This research adds to the understanding of the influence of code-mixing in social media on brand image in a multicultural society.